Analisis Promosi Jabatan Berbasis Kesetaraan Gender Pada Birokrasi Pemerintahan - Luckyto, Mukhammad; Oktaviana, Sinka; Fu'adah, Laily (IJTIMAIYA: Journal of Social Science and Teaching, 2021)
Gender is a social construction or form so that it can be formed or changed according to place, time or age, ethnicity, race, culture, social status, religious understanding, country, ideology, politics, law and economy. The purpose of this study was to analyze the promotion of positions with the perspective of gender equality both men and women in the government bureaucracy. The method used in this study is a library research method using a descriptive analysis approach. The result of this study is that the role or participation of women in the government bureaucratic structure has exceeded that of men and has experienced gender justice or equality, but there is still a small gap between female civil servants who are difficult for echelon pratama positions.